The Relationship of Factors Related To The Quality Of Life Of Chronic Renal Disease Patients Undergoing Hemodialysis At Dustira Hospital - Dedi Supriadi; Evangelina, Evangelina H (JURNAL KESEHATAN KARTIKA, 2021)
Chronic renal disease may cause the irreversible decline of the function of the kidneys needing therapy in the form of a transplant or hemodialysis.It may affect the quality of life of the patient, with many factors contributing to the effect, such as gender, age, education background, occupation, and the duration of hemodialysis and anemia. The study aims to explore factors related to the quality of life of chronic renal disease patients undergoing hemodialysis at Dustira Hospital.It employed the analytical survey method with a crosssectional approach.It involved all patients undergoing regular hemodialysis treatment at the Unit HemodialisaDustira Hospital (II.03.05.01) in 2018, with 37 samples fulfilling the inclusion criteria for consecutive sampling. The data was gained directly from the patients as well as their medical records.The data analysis used the uni-variate and bi-variate techniques via the chi-square test. The results showed there were no factors (namely gender, age, education background, occupation, and the duration of the treatment) with the pvalue of ≥ 0.05.It is recommended that Dustira Hospital offers counseling services and sharing programs for patients to share their experiences.Further investigations may be carried out to address more complex issues regarding the most influential factors in the quality of life.